Effects of biochar on soil respiration mediated by rainfall events: evidence from one-year field experiment in an urban forest - Haoran Zu; Zijun Deng; Xin Liu; Junyi Luo; Ying Chen; Meiling Yi; Xiao Wang; Xiaocui Liang; Xiang Zhang; Wende Yan (Ecological Processes)
Abstract Background Biochar is widely recognized for its capacity to capture and store carbon in soil attributed to its stable structure. However, in most field studies examining the effects of biochar application on soil respiration, the impact of rainfall events on the experimental outcomes has not been taken into account. To address the existing gap in this research field, we conducted a one-year study on soil respiration in an urban camphor forest and collected the data of soil respiration, soil temperature, soil moisture, and the rainfall events closest to the soil respiration monitoring time. We specifically examined how different stages of rainfall events influenced soil respiration in relation to biochar application. Results This study found that the annual average soil respiration rate increased with the doses of biochar application, and the soil respiration rate under the biochar application at the dose of 45 t/ha showed a significant rise. The stages of rainfall events, rainfall amount, and the interaction effect of the two, and biochar doses significantly affected soil respiration. The parameters in the regression model for soil respiration, soil temperature and moisture varied with the different stages of rainfall events and the doses of biochar application. The biochar application eliminated the significant effect of soil moisture on soil respiration during one day after rainfall events. The significant correlation between soil moisture and the temperature sensitivity of soil respiration (Q 10) was eliminated by biochar application, both during one day after rainfall events and more than eight days after rainfall events. Conclusions Our findings indicated that the rice straw biochar application has a short-term positive effect on soil respiration in urban camphor forests. The rainfall events affect the field soil respiration monitored in the biochar applications, possibly by affecting the soil respiration response to soil temperature and moisture under different doses of biochar application. The impact of rainfall events on soil respiration in biochar application experiments should be considered in future forest monitoring management and practice.